Primary Systemic Amyloidosis: a Case Report and Review of Clinical Features - HQ, Hu; SC, Wang; X, Cao; BZ , Cao (IIUM Medical Journal Malaysia, 2010)
Primary systemic amyloidosis is a rare disorder that has multisystemic manifestations. The diagnosis is very difficult because of non-specific clinical signs. We report a patient with primary systemic amyloidosis manifesting as peripheral neuropathy, nephrotic syndrome, gastrointestinal syndrome, orthostatic hypotension, pericardial fluid, weight loss and so on. Histopathological examination of kidney and sural nerve showed Congo red positive deposits. Primary systemic amyloidosis should be considered in any patient older than 40 years who has the following symptoms and signs: fatigue, weight loss, edema, paresthesias, muscle weakness, noninfectious diarrhea, skin and soft-tissue lesions, and the complications of nephrotic syndrome, congestive heart failure (not on an ischemic basis), peripheral neuropathy, or unexplained hepatomegaly. All patients need the diagnosis confirmed histologically by biopsy of an involved organ.